2017
DOI: 10.19045/bspab.2017.60021
|View full text |Cite
|
Sign up to set email alerts
|

Determination of lead in guava (Psidium guajava) planted near Sagian Wala Bypass, Lahore

Abstract: The present study deals with the determination of lead (Pb) in Guava Planted along Sagian Wala Bypass, Lahore. Samples of guava were collected from different sites of Sigan Wala Bypass. The samples were subjected to wet digestion procedure. The concentrations of Pb in 20 composite samples were determined by using Atomic Absorption Spectrophotometer (AAS). The results of this survey showed that the average concentrations detected were ranged from 6.57 to 13.10 mg/kg. Concentration of Pb in all samples was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Yami et al [23] reported that the metal concentrations (mg/kg dry weight) in the edible portion of guava collected from Nura Era Farm of Ethiopia as Cu (1.20), Zn (1.40), and Fe (5.60). Another study in Pakistan by Abrar et al [24] discovered that the values of Pb in guava planted along Sagian Wala Bypass, Lahore, were ranged from 6.57 to 13.10 mg/kg. Thus, it is sensible to assume that guava is a good heavy metal accumulator.…”
Section: Metals In the Guavamentioning
confidence: 99%
See 1 more Smart Citation
“…Yami et al [23] reported that the metal concentrations (mg/kg dry weight) in the edible portion of guava collected from Nura Era Farm of Ethiopia as Cu (1.20), Zn (1.40), and Fe (5.60). Another study in Pakistan by Abrar et al [24] discovered that the values of Pb in guava planted along Sagian Wala Bypass, Lahore, were ranged from 6.57 to 13.10 mg/kg. Thus, it is sensible to assume that guava is a good heavy metal accumulator.…”
Section: Metals In the Guavamentioning
confidence: 99%
“…Many countries have conducted regular monitoring to establish information on heavy metals in food. Numerous papers have documented the metals concentration in the fruits [6][7][8][9] and vegetables [4,[10][11][12][13][14][15][16][17][18][19][20], yet only a few in edible guavas [7,[21][22][23][24]. Thus, it is essential to evaluate the chemical composition of this guava and make known of their impact on public health.…”
Section: Introductionmentioning
confidence: 99%